2017
DOI: 10.2147/mder.s127133
|View full text |Cite
|
Sign up to set email alerts
|

The ROI-C zero-profile anchored spacer for anterior cervical discectomy and fusion: biomechanical profile and clinical outcomes

Abstract: IntroductionAnterior cervical discectomy and fusion (ACDF) has been the gold standard for treating cervical degenerative disc disease (cDDD). The use of anterior plates in ACDF poses an increased risk of complications such as screw or plate dislodgement, soft tissue injury, esophagus perforation, and dysphagia. The ROI-C™ implant system consists of a zero-profile interbody fusion cage with self-locking plates designed for stand-alone fusion without external plates or screws.ObjectiveThe purpose of this report … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 53 publications
(49 reference statements)
5
20
0
Order By: Relevance
“…Similar observations have been reported in some studies evaluating the clinical efficacy of ACDF using cages with an integrated fixation system. [ 2 3 5 7 12 13 14 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar observations have been reported in some studies evaluating the clinical efficacy of ACDF using cages with an integrated fixation system. [ 2 3 5 7 12 13 14 ]…”
Section: Discussionmentioning
confidence: 99%
“…A dysphagia rate of 2% is low compared to plate-augmented ACDF in the literature. [ 12 ] The results obtained are by the results of a recent meta-analysis showing that zero-profile anchored cages had a lower risk of postoperative dysphagia than cages with anterior plate fixation after ACDF. [ 6 ] Furthermore, although subsidence is one of the major concerns when using cages without plate fixation, the present study reported no case of subsidence in the follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the postoperative cervical cobb angle of the two surgery was signi cantly bigger than the preoperative cervical cobb angle, which indicated that both surgery can correct cervical kyphosis. Therefore, the fusion and biomechanical stability of ROI-C are equal to those of ACDF, and satisfactory surgical results of both surgery have been achieved [13] . The results of this study showed that JOA score and NDI score of both groups were improved, and good operation effect was maintained during the follow-up period, which demonstrated that the two surgery can relieve spinal cord and nerve compression, and improve the quality of life of patients.…”
Section: Discussionmentioning
confidence: 97%
“…The incidence of pharyngoesophageal perforation varies between 0.25 and 1.49% [14]. Other complications of soft-tissue injury [8], nerve injury, loss of fixation [9], degeneration of adjacent segments [10], screw plate migration and pullout, and pharyngeal perforation [12] have been documented.…”
Section: Discussionmentioning
confidence: 99%
“…The use of plates in ACDF has shown improved clinical outcomes, fusion rates, stability and prevention of graft dislodgement as well as the restoration of the cervical physiological curvature [ 7 ]. Despite the relative safety and efficacy of ACDF, many complications such as soft-tissue injury [ 8 ], loss of fixation [ 9 ], degeneration of adjacent segments [ 10 ], dysphagia [ 11 ] and pharyngeal perforation [ 12 ] have been reported.…”
Section: Introductionmentioning
confidence: 99%